Effect of plant sterols and dietary fiber among Filipino adults with moderately raised serum cholesterol level - Cayabyab, Babylyn D. (2012)
Background: Filipino households have shown significant changes in dietary patterns i.e. increasing intakes of fats and oils (also increased in saturated fat and cholesterol intakes), sugar, syrups, meats and processed food (animal products) and declining fruits and vegetables (NNS, FNRI-DOST,2008). The increasing urbanization in the country coupled with an increase in per capita income is a reflection of these dietary pattern changes (Pedro et.al,2003). Cardiovascular disease(CVD) is the leading cause of death in the country (Philippine Statistics, DOH,2006). Data on increasing trend of high total country cholesterol (TC) and high LDL-c levels among Filipino adults, the known as risks factors for CVD may be considered alarming (NNS,FNRI-DOST,2008). One of the major preventive measures to control cardiovascular disease is the management of high TC and LDL-c through healthy diet (Rofles et al, 2006. Plant sterols and dietary fiber are food components with known cholesterol lowering functions. They have gained promising positions in international in dietary guideline (FDA,2000; ATP III, 2001) . The study intends to determine the effects of plant sterol, dietary fiber and the combination of the two food components on the TC and LDL-c of Filipino adults with moderately raised serum cholesterol levels. Double-blind randomized pre post test placebo-controlled study design was used. Seventy-five (75) respondents were divided into four groups: plant sterol group (n=18); dietary fiber group (n=19); combined group (n=19) and placebo group (n=19). They were asked to consume different product combinations in a period of four weeks which essentially contain 1.2 g of plant sterol, with 3.5 totla dietary fiber, the combination of the two food items and test product without plant sterol and dietary fiber, respectively. Blood lipid parameters i.e. TC and LDL-c were assessed at baseline and after four weeks. After four weeks of feeding, the plant sterol group showed significant reductions in TC and LDL-c with 7.2% and 12.1% respectively, (p<0.0001). The dietary fiber group showed LDL-c reduction of 0.6% and a significant increase of 0.1% in TC (p<0.0001). The combined group showed significant TC and LD-c reductions of 4% and 6.4%,respectively (p<0.0001). Comparing the three treatment groups to the placebo group at end line, the plant sterol group showed significant TC and LDl-c reductions of 12.3% and 17.3% respectively (p<0.05).The combined group showed significant decrease in TC and LDL-c levels by 8.8% and 12.9% respectively (p<0.05). At end line, significant increases were also seen for mean HDL-c concentrations of the dietary fiber and combined groups by 1.61 mg/dl (3.2%) and 0.37 mg/dl (0.71%) respectively,while the plant sterol group showed a significant decrease of 0.04 mg/dl (0.08%) compared to baseline (p<0.0001). Compared to the placebo group at endline, the dietary fiber and combine groups' mean HDL-c levels were significantly higher by 5.24 mg/dl (11%) and 5.20 mg/dl (11%) respectively, (p<0.05). Plant sterol is effective in reducing TC and LDL-c. Dietary fiber is less effective than plant sterol in reducing TC and LDL-c but showed an increase in HDL-c level. The combination of plant sterol and dietary fiber was effective in decreasing C and LDL-c and increasing HDL-c concentrations.